2005
DOI: 10.2108/zsj.22.213
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Sandwich ELISA System to Detect Diapause Hormone, and Developmental Profile of Hormone Levels in Egg and Subesophageal Ganglion of the Silkworm, Bombyx mori

Abstract: In the silkworm Bombyx mori, diapause hormone (DH) is produced in the female subesophageal ganglion (SG) and induces embryonic diapause by targeting developing ovaries. DH is processed from a precursor protein consisting of DH, pheromone biosynthesis activating neuropeptide (PBAN) and three other neuropeptides (SGNPs). Because these five neuropeptides share a common sequence, FXPRLamide, at the C-terminus, a direct and specific assay for DH itself is required in order to understand the profile of concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…The DH content in the brain-SG complex has previously been shown to decrease from the middle pupal stage in both diapause types (Kitagawa et al 2005). Therefore, these results suggest that FXPRLa peptides are actively transported from the SG, although the precise developmental rate of FXPRLa biosynthesis remains unknown.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The DH content in the brain-SG complex has previously been shown to decrease from the middle pupal stage in both diapause types (Kitagawa et al 2005). Therefore, these results suggest that FXPRLa peptides are actively transported from the SG, although the precise developmental rate of FXPRLa biosynthesis remains unknown.…”
Section: Discussionmentioning
confidence: 65%
“…At the middle pupal stage, DH levels in the SG and SG-brain complex are markedly decreased in the DEP as compared with those of the NDEP (Kitagawa et al 2005). Furthermore, significant morphological and functional differences in the three neuromeres of the DHPCs have been detected following surgical ablation experiments (Ichikawa et al 1996) and electrophysiology experiments involving changes in firing activity patterns between DEP and NDEP (Ichikawa and Kamimoto 2003;Ichikawa 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DH acts on a G protein-coupled receptor in the developing ovaries of females during pupal-adult development (12,13), and is produced in DH-pheromone-biosynthesis-activating neuropeptide-producing neurosecretory cells (DHPCs) located within the subesophageal ganglion (SG) (14)(15)(16). DH levels in the SG and SG-brain complex are markedly lower in 25DD pupae than in 15DD pupae, although level of mRNA expression is higher in 25DD than in the 15DD pupae at the early to middle stages of pupal-adult development (11,17). The labial neuromere cell of the SG (SLb) somata are DHPCs, and transport of DH from the Significance Diapause has evolved as a specific subtype of dormancy in most insect species and as a seasonal polyphenism that ensures survival under unfavorable environmental conditions and synchronizes populations.…”
mentioning
confidence: 99%
“…Interestingly, the tenidium formation and late stages of embryogensis are sensitive periods for receiving environmental signals to determine whether its offsprings are diapause or non-diapause (Hasegawa, 1957;Yamashita and Hasegawa, 1985). Meanwhile, pupal-adult development is a key stage during which DH is synthesized and secreted that leads to the egg diapause (Yamashita and Hasegawa, 1985;Kitagawa et al, 2005). The sustained high expression of the BmCREB in the diapause type silkworm, especially at the two critical stages suggested that the activation of BmCREB in transcriptional level is related to the diapause signal reception in embryogenesis and retrieval in pupal stage.…”
Section: Discussionmentioning
confidence: 99%